Organizational Culture as a Factor in the Successful Implementation of Organizational Changes - Belak, Stipe; Ušljebrka, Ivana (Oeconomica Jadertina, 2017)
This paper theoretically proves that the organizational culture is a key factor for a successful implementation of organizational changes. Looking at the dynamic environment in which today's business organizations exist, it is clear that organizational changes have become a necessity needed for their survival. It does not matter whether it is a minor improvement of the peripheral segment of the organization or its complete transformation – what is inevitable is the change of the human factor. Since man is by nature an inert being, likes security, routines and certainty, it tends to oppose any changes, especially when it comes to radical changes in which his participation is minimal, if any. In such a situation, in order to reduce the human resistance to changes to a minimum, and achieve the willingness of employees to change, it is necessary to influence their attitudes, mindset and behavior. The organizational culture plays a key role in this process. The organizational culture through its values, beliefs, customs and norms shapes the behavior and attitudes of people within an organization, influences the readiness to change, as well as its later successful implementation. The paper concludes that the manager, prior to the implementation of organizational changes, should carry out a cultural analysis and then institutionalize those organizational values that encourage the construction of a positive attitude toward organizational change, as well as the building of organizational commitment and the trust in the management.
Keywords: organizational change; revolutionary changes; the resistance of employees; organizational culture; organizational values; organizational commitment; organizational trust